Vitrification with DAP 213 and Cryotop of Ex Situ and In Situ Feline Cumulus-Oocyte Complexes - Alves, A. E.; Kozel, A. C.; Luvoni, G. C. (Wiley-Blackwell, 2012)
This study was undertaken to compare cryotolerance, in terms of viability and resumption of meiosis after warming and culture (24 and 48 h), of ex situ (isolated) and in situ (enclosed in the ovarian tissue) feline cumulusoocyte complexes (COCs) vitrified with DAP 213 (2 M DMSO, 1 M acetamide, 3 M propylene glycol) in cryotubes or Cryotop method. Ovaries were harvested from 49 pubertal queens. of each pair of ovaries, one was dissected to release COCs randomly divided into three groups: fresh COCs (control), ex situ COCs vitrified with DAP 213 and Cryotop. The cortex of the other ovary was sectioned into small fragments (approximately 1.5 mm3) and randomly assigned to be vitrified by DAP 213 or Cryotop. After warming, ex situ and in situ (retrieved form vitrified ovarian tissue) COCs were matured in vitro. Viability of oocytes was highly preserved after warming and culture in all treatments. Proportions of oocytes surrounded by complete layers of viable cumulus cells were remarkably decreased (p < 0.00001) in both vitrification procedures compared to fresh oocytes. Resumption of meiosis occurred in all treatments. After 24 h of culture, results were similar in ex situ and in situ vitrified oocytes regardless of the vitrification protocol used (range 29-40%), albeit lower (p < 0.05) than those of fresh oocytes (65.8%). After 48 h of culture, ex situ oocytes vitrified with Cryotop achieved the rates of meiosis resumption similar to fresh oocytes (53.8% vs 67.5%; p > 0.05) and ex situ and in situ oocytes vitrified with DAP 213 showed similar rates of resumption of meiosis. These findings demonstrated that DAP 213 and Cryotop preserve the viability of ex situ and in situ oocytes, but cumulus cells are highly susceptible to vitrification. However, the capability to resume meiosis evidences that feline immature oocytes vitrified as isolated or enclosed in the ovarian cortex have comparable cryotolerance.